Pelatihan Pembuatan Saus Cabai di Desa Lubuk Cuik Kabupaten Batu Bara: Training on Making Chili Sauce in Lubuk Cuik Village, Batu Bara Regency - Togar Timoteus Gultom; Indrayani Indrayani; Arfis A; Mulia Mulia; Suhelmi Suhelmi; Hendra Susilo (Edujavare Publishing, 2024)
Villages are often a source of abundance of raw materials such as chilies, but the lack of knowledge and skills in processing them into value-added products hinders the economic potential they can achieve. This service research aims to empower village communities through training in making quality chili sauce. The service method applied is Community Based Research (CBR) with a Forum Group Discussion (FGD) approach. The findings show that this training was successful in increasing the village community's income through increasing the added value of products and wider market access. Apart from that, training participants also experience increased skills in food processing and build stronger community networks. The discussion analysis links research findings with previous research and relevant theories regarding rural economic empowerment. In conclusion, training in making chili sauce in villages has great potential to improve economic and social welfare at the village level, by paying attention to economic, social and environmental aspects holistically.